2017
DOI: 10.3748/wjg.v23.i18.3367
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility testing before first-line treatment for Helicobacter pylori infection in patients with dual or triple antibiotic resistance

Abstract: AIMTo evaluate the efficacy of antimicrobial susceptibility-guided therapy before first-line treatment for infection in patients with dual or triple antibiotic resistance.METHODSA total of 1034 patients infected by Helicobacter pylori (H. pylori) during 2013-2014 were tested for antimicrobial susceptibility. 157 of 1034 (15%) patients showed resistance to two (127/1034; 12%) and to three (30/1034; 3%) antibiotics. Sixty-eight patients with dual H. pylori-resistance (clarithromycin, metronidazole or levofloxaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
17
1
Order By: Relevance
“…There was no significant difference in eradication rates between treatment‐naive and treatment‐experienced groups . This, however, is at odds with a Spanish study which found significantly higher eradication rates (83% vs 33%) in culture‐guided therapy in treatment‐naïve patients …”
Section: Culture‐guided Treatmentcontrasting
confidence: 57%
See 3 more Smart Citations
“…There was no significant difference in eradication rates between treatment‐naive and treatment‐experienced groups . This, however, is at odds with a Spanish study which found significantly higher eradication rates (83% vs 33%) in culture‐guided therapy in treatment‐naïve patients …”
Section: Culture‐guided Treatmentcontrasting
confidence: 57%
“…61 This, however, is at odds with a Spanish study which found significantly higher eradication rates (83% vs 33%) in culture-guided therapy in treatment-naïve patients. 10 An Italian study comparing sequential and bismuth-based therapy did not find that the pattern of bacterial resistance significantly affected eradication rates. Dual resistance to clarithromycin and amoxicillin did, however, lower eradication rates in both treatment strategies.…”
Section: Culture-g U Ided Tre Atmentmentioning
confidence: 98%
See 2 more Smart Citations
“…In the Microbiology Department of HUD (San Sebastian), cultures are carried out “as routine practice” since 1994 . During the period 2000‐2012, resistance to two or three antimicrobials was around 12.5% for dual resistance and 2.9% for triple resistance …”
Section: Discussionmentioning
confidence: 89%